The Effect Of Work Motivation, Human Relation, Work Discipline, And Work Ethos On The Performance Of Polri - Rona Tanjung; Mulyadi Mulyadi; Hutri Agus Romi; Moch Aminudin Hadi; Jazuli Jazuli (Cita Konsultindo Research Center, 2022)
This study aims to determine how the influence of leadership, work facilities, work discipline, and work motivation on the performance of Polri members in the Barelang Police Intelligence Unit in Batam. This type of research is quantitative research. Sampling in this study were all members of the Police in the Intelkam Unit Polresta Barelang Batam, as many as 45 respondents with sampling using saturation sampling technique. The data obtained in this study using a google form that has been tested for validity and reliability. These results show that the variables of work motivation, human relations, work discipline and work ethic together have a significant effect on the performance of members of the police.